Integrating Spiritual Counseling into Family Therapy: A Qualitative Study with Psychological Counselors in Turkey - Okan, Nesrullah; Şahin, Yahya (Halil Eksi, 2026)
The purpose of this study is to examine how family therapists experience spirituality in the family therapy process, how they integrate it with systemic family therapy models, and how this process is interpreted within Turkey’s cultural context. The research was theoretically grounded within the frameworks of Bowen Family Systems Theory, Structural Family Therapy, and Satir Transformational Systemic Therapy models; it was conducted using the Interpretative Phenomenological Analysis (IPA) approach, one of the qualitative research designs. The participants in the study consisted of 14 therapists who actively practice family or couple therapy in Turkey and have worked with cases where spirituality themes have come up in the therapy process. Data were collected through semi-structured in-depth interviews and analyzed according to the interpretative analysis steps of IPA. The analysis revealed seven main themes regarding the position and function of spirituality in family therapy. The findings show that spirituality is not merely an individual belief system within the family system; it is a central relational structure that shapes family members’ worlds of meaning, emotional regulation processes, roles, boundaries, and ways of coping with crises. It was found that spirituality strengthens emotional resilience and intra-family bonds through themes such as prayer, gratitude, forgiveness, and patience; however, in some cases, it can also reinforce guilt, pressure, and rigid hierarchies. Participants emphasized that spirituality naturally intersects with intergenerational transmission and differentiation processes in the Bowen model, with boundaries and hierarchy in the Minuchin model, and with self-worth and emotional transformation in the Satir model. However, therapists indicated that they encountered significant challenges when working with spirituality, such as maintaining therapeutic neutrality, role confusion, and managing ethical boundaries. In conclusion, this study reveals that spirituality is an inevitable and two-way component of the family therapy process in the Turkish context. The findings highlight the need for a spiritually integrated systemic family therapy model that is culturally sensitive, ethically clear, hope-based, and inclusive of children; it offers a culturally grounded and original contribution to the family therapy literature. ©Copyright 2026 by Author(s)
Keywords: cultural context; family therapy; qualitative research; Spirituality; systemic approaches